Uncomplicated full-term birth after laparoscopical salpingotomy as organ-preserving therapy of naturally conceived heterotopic pregnancy: A case report - Roland Csorba; Antonella Iannaccone; Panagiotis Tsikouras; Saed Almasarweh (SAGE Open Medical Case Reports)
Heterotopic pregnancy, the simultaneous occurrence of intrauterine and extrauterine gestations, is a rare phenomenon, especially without a history of assisted reproduction. This case report describes a 33-year-old woman presenting with severe abdominal pain at 7 weeks of pregnancy. Transvaginal ultrasound revealed an intrauterine singleton pregnancy and an adnexal mass, highly suspicious of an ectopic pregnancy, along with significant intraperitoneal fluid. Emergency laparoscopy confirmed intra-abdominal hemorrhage and a near rupture of the left fallopian tube. A laparoscopic salpingotomy successfully resolved the ectopic pregnancy while preserving the intrauterine pregnancy. Postoperative course was uneventful. The patient later delivered a healthy infant at term. This case highlights the importance of considering heterotopic pregnancy in patients with confirmed intrauterine pregnancy, even in the absence of assisted reproductive technologies and other risk factors.